Actual Management in Islamic Higher Education: The New Insight in Management Science - Samian, Supendi; Karim, Abdul; Zaldi, Ahmad; DZ, Abdus Salam; Norman, Efrita; Iskandar, Nur Muhamad (Program Pascasarjana, Universitas Islam Bunga Bangsa Cirebon, 2025)
One of discuse of Islamic Higher Eduction (IHE) management is administration that always regarding of management. Management still widing and this study is facing new insight of administration in actual management in education that lack in preview research. The goal of this newsletter is to set up a basis for understanding the demanding situations related to IHE.The gift observe explores the efficacy of experiential getting to know withinside the context of control education, which is usually applied to non-educational discussions. This studi is literature review uses PRISMA analysis with reduction and content analysis, display and conclution. Data credibily is using triangulation, transferability and depenability. Result is 600 article is found from keyword after exclude, found only 5 about actual management in title and 18 relevant to the keyword written in the title implisitly. lack of literature spesifict display of this title directly related to education. Above 75% Technology-assisted IHE can improve graduate quality and efficiency. Insight of this research is administration is one of important thing in actual management. Limitation of this research is lact from field data. This research significantly impacts the field of IHE by reorienting scholarly attention toward the critical intersection of administration and actual management—an area previously overlooked despite its fundamental importance to institutional effectiveness. Future research should prioritize a comprehensive multi-institutional investigation that combines quantitative metrics with qualitative insights from stakeholders across diverse IHE settings, focusing particularly on how administrative modernization can be implemented while honoring Islamic educational principles